2018
DOI: 10.1088/1674-1137/42/12/123110
|View full text |Cite
|
Sign up to set email alerts
|

Conformal field theory on the horizon of a BTZ black hole

Abstract: In three dimensional spacetime with negative cosmology constant, the general relativity can be written as two copies of SO(2, 1) Chern-Simons theory. On a manifold with boundary the Chern-Simons theory induces a conformal field theory-WZW theory on the boundary. In this paper, it is show that with suitable boundary condition for BTZ black hole, the WZW theory can reduce to a massless scalar field on the horizon. *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…As was shown in Ref. [13], those boundary degrees of freedom can be described by two chiral massless scalar fields Ψ L (for left-moving) and Ψ R (for right-moving). From the analysis of the quasi-particles, it was shown that the BTZ black holes can be consider as the fractional quantum Hall states with filling factor v = 1 2k [14].…”
Section: Topological Order In 3d Ads Gravitymentioning
confidence: 66%
“…As was shown in Ref. [13], those boundary degrees of freedom can be described by two chiral massless scalar fields Ψ L (for left-moving) and Ψ R (for right-moving). From the analysis of the quasi-particles, it was shown that the BTZ black holes can be consider as the fractional quantum Hall states with filling factor v = 1 2k [14].…”
Section: Topological Order In 3d Ads Gravitymentioning
confidence: 66%
“…So for black holes, the corresponding algebra is W = U (1) ⊗ Ū (1) which have opposite chirality. This result can also be obtained from the Chern-Simons theory [30]. Now we considered the representation of this algebra W = U (1) ⊗ Ū (1) [31].…”
Section: Near Horizon Symmetry Algebra From W1+∞ Symmetry Algebramentioning
confidence: 70%
“…[6,7]. The boundary modes on the horizon of a BTZ black hole can be described by two chiral massless scalar fields with opposite chirality [8]. This is the same as a topological insulator in three dimensional spacetime (also called quantum spin Hall state) [9].…”
Section: Introductionmentioning
confidence: 99%